Database Autopsy a Close Look to Database Auditing For Oracle Database (Global Journal of Computer Science and Technology, 2013)
Today, that business has different rules and regulation and supplied threats; organizations must go well beyond securing their data, and managing their database. Essentially, Data have to be perpetually monitored to be aware of who what, to all their data. Database auditing involves monitoring database to be aware of what user of proceedings. In this article we will offer a novel procedure for finding auditing records from different locations that DBMS keeps records, further more we will discuss which user, or system activity to keep records to do auditing efficiently and also avoid over use of system resources which will caused on slow transaction time.